Implementation of a mock root cause analysis to provide simulated patient safety training. Issue 2 (31st October 2017) - Murphy, Martina; Duff, Jennifer; Whitney, Julie; Canales, Benjamin; Markham, Merry-Jennifer; Close, Julia
Abstract : Background: The proposed revision to the Accreditation Council for Graduate Medical Education (ACGME) Common Program Requirements includes participation in real or simulated patient safety activities, such as root cause analysis (RCA).1 Because exposure to RCA may occur with low frequency, a mock RCA was developed and piloted for feasibility with Hematology/Oncology fellows. Objective: To improve trainee knowledge of the goals and application of RCA in patient safety and quality improvement through a simulated experience. Methods: A mock RCA was implemented with Hematology/Oncology fellows over two subsequent years. In small groups, they reviewed a case involving an adverse event and identified sources of harm. Additional details, in the form of provider interviews, were available upon request. Trainees identified the root cause(s) and proposed measurable changes. Teams presented proposals to peers and a panel representing hospital leadership. Feedback was provided. Trainees completed evaluations and were surveyed regarding their perceptions. Results: Thirteen of 15 fellows completed the survey. Twelve of 13 (92%) fellows felt the mock RCA improved their comfort level for participation in a real RCA. Ten of 13 fellows (77%) reported increased awareness and likelihood of reporting near misses and/or adverse events following participation. More thorough patient care documentation following the session was reported by 8 of 13 (62%). Conclusion: A pilot trial of a mock RCA with Hematology/Oncology fellows had high trainee satisfaction. Post-session surveys and informal interviews suggest trainees have reduced anxiety when faced with participation in a real RCA and have more interest in the process after participation.